Care of surgical infections by Médecins Sans Frontières Operations Centre Brussels in 2008–14. (27th April 2015) - Sharma, Davina; Hayman, Kate; Stewart, Barclay T; Dominguez, Lynette; Trelles, Miguel; Saqeb, Sanaulhaq; Kasonga, Cheride; Hangi, Theophile Kubuya; Mupenda, Jerome; Naseer, Aamer; Wong, Evan; Kushner, Adam L
Abstract: Background: Surgical infections represent a substantial yet undefined burden of disease in low-income and middle-income countries (LMICs). Médecins Sans Frontières (MSF) provides surgical care in LMICs and collects data useful to describe the operative epidemiology of surgical need that would otherwise be unmet by national health services. We aimed to describe the experience of MSF Operations Centre Brussels surgery for infections during crisis; aid effective resource allocation; prepare humanitarian surgical staff; and further characterise unmet surgical needs in LMICs. Methods: We reviewed all procedures undertaken in operating theatres at facilities run by the MSF Operations Centre Brussels between July, 2008, and June, 2014. Projects providing only specialty care were excluded. Procedures for infections were quantified, related to demographics and reason for humanitarian response was described. Findings: 96 239 operations were undertaken at 27 MSF Operations Centre Brussels sites in 15 countries. Of 61 177 general operations, 7762 (13%) were for infections. Operations for skin and soft tissue infections were the most common (64%), followed by intra-abdominal (26%), orthopaedic (6%), and tropical infections (3%). The proportion of operations for skin and soft tissue infections was highest during natural disaster missions, intra-abdominal infections during hospital support missions, and orthopaedic infections during conflict missions. Most procedures for skin and soft tissue infections were minor (76%), whereas most operations for intra-abdominal infections were major (98%). Interpretation: Surgical infections are among the most common causes for operation in LMICs. Although many procedures were minor, they represent substantial use of perioperative resources. Growing evidence shows the need for improved perioperative capacity to aptly care for the volume and variety of conditions comprising the global burden of surgical disease. Funding: Médecins Sans Frontières.